Application of simulation methods to evaluation of accoustic features and design of adaptation of the concert hall of Cracow Philharmonic Orchestra - GOŁAŚ, A.; WIERZBICKI, J. (Archives of Acoustics, 1993)
The publication presents the problems of application of digital methods of simulation of acoustic field to the evaluation of the acoustic characteristic and adaptation of the concert hall of the Cracow Philharmonic Orchestra. The measurement method based on an advanced technique of signal processing and the results obtained have been described. The evaluation of acoustic properties of the hall was carried out according to the Beranek Scale. A geometric model of acoustic field has been presented, as well as the acoustic parameters determined. An assessment method according to Ando has been discussed. This method has been applied in order to determine the influence of the changes in stage arrangement and kind of the music performed on the hearing conditions. Directions of further research based on the experimental and digital simulation methods have been proposed.